Three-Layered Stacking Process by Au/SiO2 Hybrid Bonding for 3D Structured Image Sensors. (1st August 2017) - Honda, Yuki; Goto, Masahide; Watabe, Toshihisa; Hagiwara, Kei; Nanba, Masakazu; Iguchi, Yoshinori; Saraya, Takuya; Kobayashi, Masaharu; Higurashi, Eiji; Toshiyoshi, Hiroshi; Hiramoto, Toshiro
Abstract : In this study, a 3D structured CMOS image sensor that can process signals pixelwise in parallel is investigated as a means to simultaneously increase the pixel count and frame rate. To enhance sensor performance beyond current technologies, higher integration via multilayer stacking is essential. We developed a multilayering technique based on repetitive Au electrode embedding, direct bonding, and Si substrate removal processes. To this end, we fabricated a three-layered daisy-chain test device with 6-μm-pitch Au electrodes. Experimental results show that the series of electrical interconnections exceeds 986, 000 contacts with an Au contact resistance of ~92.8 mΩ for a single connection.